(untitled) (Research, Society and Development, 2022)
The total Brazilian population was estimated at 212.7 million in 2021 and for the year 2030, it is estimated to reach 40 million elderly people. With this growth, the search for strategies that allow healthy aging is necessary and thus, technology through applications has been used as an ally in the intervention of the cognitive effects arising from age. The study aimed to analyze the collection of mobile applications developed for the elderly in order to promote benefits against the deleterious effects of the dementia process. For this, a search was carried out in the databases “LILACS”, “SciELO”, “PUBMED” and “PKP (Publik Knowledge Project)”, through the Boolean combination of the descriptors: (elderly OR aged OR “old man”) AND (“virtual reality” OR “mobile applications” OR “mobile app” OR app) AND (“cognitive deficit” OR “memory disorders” OR “cogniti”). Obtaining as inclusion criteria articles corresponding to the year 2016 to 2021 and articles on mobile applications aimed at prevention or cognitive stimulation of elderly people in the process of dementia. In this way, the existence of three applications was found, which, when tested, showed advantages in terms of their applicability to the advancement of the elderly in the dementia stage, showing favorable results in the improvement of cognitive functions such as memory, attention and logical reasoning. Therefore, it is clear that the digital world is favorable to healthy aging.